Comportamento da proteção de sobrecorrente em redes com geração distribuída operando em ilhamento intencional - Paula, Toribio Cruvinel de (2024)
Distributed generation (DG) has become a fundamental part of the modern electrical system, especially with the increasing adoption of renewable energy sources such as solar and wind. However, the integration of DG presents significant challenges for the protection of distribution systems, particularly in islanding situations, where the isolated operation of microgrids can compromise the coordination of protection devices. Despite advancements in protection technology, there are still gaps in understanding how DG affects the coordination of overcurrent protections, resulting in operational failures and safety risks. Existing automated solutions have not proven to be sufficiently effective in addressing the complexities introduced by DG, especially in islanded operation scenarios. This work proposes a detailed analysis of the impacts of islanding in microgrids with GDFV from the perspective of overcurrent protection. The methodology involves simulations in a representative environment that incorporates industrial loads and photovoltaic generation, using MATLAB/Simulink software to model the behavior of protection devices under different operating conditions. The results indicate that the integration of distributed photovoltaic generation requires a reassessment and adjustment of existing protection systems to ensure the continuity and safety of distribution network operations. The implementation of adaptive technologies and the strategic use of new protection functions are essential to address the challenges posed by this new energy configuration